Impacts of the Covid-19 pandemic on Psychology professionals (Research, Society and Development, 2021)
The pandemic caused by the Sars-CoV-2 coronavirus has placed health professionals in constant challenge. Thus, with the psychology professional inserted in this context, it is important to understand the impacts arising from this scenario. In view of the scarcity of research on the subject so far, the objective was to verify what impacts the pandemic has caused for psychologists who are working on the front lines in the hospital and clinic. To this end, an integrative literature review was carried out, based on the search for scientific publications indexed on the Google Scholar platform, in the journal of the Coordination for the Improvement of Higher Education Personnel, in the Scientific Eletronic Librabry Online and in the databases of the Latin American and Caribbean Literature on Health Sciences and Portal of Electronic Journals on Psychology, both inserted in the Virtual Health Library. This resulted in the selection of four articles for this review. In view of the findings, the development of symptoms related to stress, anxiety, depression and substance abuse was noticed in psychology professionals. In addition, the psychologist finds difficulties in relation to flow, emergency and contact with patients, in order to also have to quickly adapt to the reality of online care for psychological intervention. This research allowed us to reflect on the need for careful observation with psychologists regarding traumatic and social problems generated by the pandemic. In addition, there was a need for further studies to expand the panorama of impacts beyond the psychologists who work in tertiary and clinical care.